PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN DAN MINAT BELI ULANG SMARTPHONE OPPO - Ramdhani, Desti; Suzy Widyasari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this research is to test and analyze the effect of product quality, price perception and brand image on consumer satisfaction and consumer satisfaction on the interest in repurchasing OPPO Smartphones in Pati. The object of this research is OPPO Smartphone users. This study used a data collection tool in the form of a questionnaire. Samples were taken as many as 100 respondents, namely consumers who have purchased OPPO Smartphone products. Determination of the sample by purposive sampling technique. All questions were measured on a Likert scale. The research data analysis method used multiple linear regression. The data is processed using the SPSS program. Based on the results of this study, it can be concluded that product quality has a positive and significant effect on consumer satisfaction, price perception has no effect on consumer satisfaction, brand image has a positive and significant effect on consumer satisfaction and consumer satisfaction has a positive and significant effect on repurchase intention..